Retinopathy of prematurity and its association with neonatal factors (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Retinopathy of prematurity is considered as an important cause of blindness. This prospective study was undertaken to document the frequency and the associated factors of retinopathy of prematurity among 97 preterm newborn weighing